Factors that Influence Performance Assessment of the Number of Seafarer Requests in the Manning Agency - Akbar, Muhammad; Achmadi, Tri; Widya Kurniawan, Murdhifin Zulmy (Pusat Publikasi Ilmiah Institut Teknologi Sepuluh Nopember, 2024)
Manning Agency, better known as the Barombong Maritime Polytechnic, founded BMP Manning Agency as a forum for producing reliable and professional sailors in the global maritime industry. Based on the results of social and stakeholder studies as well as several literature reviews, it is known that prospective ship crews who will be transferred to Manning agency partner companies set several quality standards apart from the administration and expertise that prospective crew members have because the Manning agency's task is to prepare ship crews, so this aspect is also a significant concern in addition to the theory of expertise required. For this reason, this research covers the problem of assessing the self-quality of seafarers, which indicates a problem and challenge that seafarers must resolve. The Manning agency and Borombong Maritime Polytechnic need to improve the image and quality, especially the number of seafarers transferred to the Company, so that they not only fulfil the requirements at the beginning but still maintain self-quality until going into the field to work. The method used is multiple linear regression, where it is known that the variables that influence the number of sailors transferred are the Discipline Level Variable (X1), the Responsibility Level Variable (X3) and the Team Cooperation Level Variable (X4) with model goodness of 74.41%. Therefore, the Manning Agency must pay more attention to these three variables.